Effects of the Bee Venom Herbal Acupuncture on the Neurotransmitters of the Rat Brain Cortex - Hyoung-Seok Yun; Jae-Dong Lee (Korean Pharmacopuncture Institute, 2001)
In order to study the effects of bee venom Herbal Acupuncture on neurotransmitters in the rat brain cortex, herbal acupuncture with bee venom group and normal saline group was performed at LI4 bilaterally of the rat. the average optical density of neurotransmitters from the cerebral cortex was analysed 30 minutes after the herbal aqupuncture, by the immunohistochemistry. The results were as follows: 1. The density of NADPH-diaphorase in bee venom group was increased significantly at the motor cortex, visual cortex, auditory cortex, cingulate cortex, retrosplenial cortex and perirhinal cortex compared to the normal saline group. 2. The average optical density of vasoactive intestinal peptide in bee venom group had significant changes at the insular cortex, retrosplenial cortex and perirhinal cortex, compared to the normal saline group. 3. The average optical density of neuropeptide-Y in bee venom group increased significantly at the visual cortex and cingulate cortex, compared to the normal saline group.